CuO nanowire@Co3O4 ultrathin nanosheet core-shell arrays: An effective catalyst for oxygen evolution reaction. (1st October 2017) - Li, Xiumin; Du, Xiao; Ma, Xuli; Wang, Zhongde; Hao, Xiaogang; Abudula, Abuliti; Yoshida, Akihiro; Guan, Guoqing
Graphical abstract: Highlights: Highly ordered CuO nanorod@Co3 O4 nanosheet core/shell array was fabricated for OER. The optimum electrocatalyst exhibited a small overpotential of 258 mV@10 mA cm −2 . Cu 2+ in CuO/Co3 O4 composite was found to be oxidized to Cu 3+ during OER process. Abstract: Well-aligned CuO nanowire@Co3 O4 nanosheet core-shell array was successfully fabricated on carbon fibers by multi-step electrodeposition combined with thermal treatment and applied as the binder- and conductive-agent-free anode for oxygen evolution reaction (OER) in water electrolysis process. Such an anode revealed an overpotential of 258 ± 3.2 mV at a current density of 10 mA cm −2 in 1.0 mol L −1 KOH solution, which is much lower than that of pure CuO nanowires or Co3 O4 nanosheets based electrode. This should be attributed to the smart hybridization of CuO nanowires and Co3 O4 nanosheets into hierarchical core/shell array configuration which could largely increase the amount of contact areas between electrolyte and active sites. Moreover, it is found that the Cu 2+ in CuO/Co3 O4 composite was oxidized to Cu 3+ components during the OER process, which should serve as the new catalytic active sites for OER. It is expected to provide a novel route to prepare such a core-shell electrocatalyst with high performance for water splitting.